Means-tested support for people approaching and beyond state pension age - Jonathan Cribb; Carl Emmerson; Heidi Karjalainen (Institute for Fiscal Studies (IFS), 2024)
This IFS Pensions Review report sets out issues with the current means-tested benefit system for those approaching the state pension age and beyond.
Keywords: 330; Savings; pensions and wealth; Ageing; Benefits; Pensioner benefits; Public finance; Retirement; Working age benefits